Analyzing the Impact of Learning and Development on Employee Engagement in Information Technology Sector - K. Malik Ali, S. Aishwarya, M. Ayishamillath (International Journal of Advanced Science and Technology, 2019)
The objective of this study is to find out the impact of learning and development on employee engagement of employees working in Information technology sector. A descriptive and analytical study is carried out at Chennai coveringinformation technology employees. The independent variables are learning and development; and employee engagement is the dependent variable for the hypothesis proposed. Simple convenience sampling used for this research purpose. Data was collected from the respondents through questionnaires. About 200 Questionnaires were distributed and collected. This study reveals that there is a significant impact of learning and development on employee engagement . Keyword:. Learning and development, Employee engagement, information technology, Learning programme design, organization strategy